Exploring six Muslim teachers’ coping strategies in overcoming mental illness - Abd Karim, Aishah Hanim (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This qualitative research explored Malaysian Muslim teachers’ perspectives of mental illness and well-being with an aim to understand how they coped with their own condition of illness and the relationship between spiritual practices and mental health. Six public school teachers served as interview participants, all of whom had experienced a mental breakdown at some point in their career. Using a semi-structured protocol, the teachers were interviewed individually at different times and settings. An inductive content analysis was used to interpret the data for all participants. The findings showed four themes, namely medical treatment, religion, family and societal support, and positivity to be the dominant factors of coping. Four subthemes emerged from religious coping, i.e., prayers, Qur’an reading, protective factor, and diseases of the heart. These subthemes suggested an association between spiritual practices and mental well-being. Apart from seeking professional help and getting appropriate medical treatment, the study also revealed the importance of engaging in various spiritual practices such as performing the five daily prayers, zikr, salawat shifa', and reading the Qur'an, strategies that produced the feelings of peace and calmness in the participants which were instrumental in helping them cope with their illness and become productive teachers.